FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN DISMENORE PADA REMAJA - Irianti, Berliana (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Primary dysmenorrhoea is defined as pain arising from myometrial dysrhythmiccontractions with one or two symptoms ranging from mild to severe pain in the lowerabdomen, buttocks and thighs. The purpose of this study is to describe the factors thatinfluence the symptoms of primary dysmenorrhoea. The factors studied were age ofmenarche, body mass index, family history, menstrual cycle and malondialdehyde (MDA)levels. This research is an observation research with Cross Sectional design to determinethe factors that cause dysmenorrhea in adolescents. The study was conducted on 23 girlsaged 17-20 years with clinical signs of primary dysmenorrhea, having dysmenorrhea inthe menstrual cycle in the past 6 months. Data were obtained using checklists andexamination of Malondialdehyde levels using Thiobarbituric Acid method. The measuringinstruments used are spectrophotometer, adult scales, microtoice, tools have been tested bythe Department of Industry and Trade UPTD Metrology Center. The factors that causedysmenorrhea can be seen from the age factor of menarche less than 12 years, body massindex factors in obese adolescents, factors in the family history of dysmenorrhea, ovulatorymenstrual cycle factors (regular) and Malondialdehide level factors <2.14 μmol/ml.Research suggestions, you should do research by linking the influencing factors,antioxidant factors in the body, doing research when 1-2 days of menstruation.Suggestions for teenagers to maintain their diet (4 healthy 5 perfect), exercise routine,healthy lifestyle. When dysmenorrhea occurs, a method can be done to reduce pain,including; by doing relaxation (yoga), acupuncture (doing massage with aromatherapy),listening to music, hypnotherapy (changing the mindset from negative to positive), the useof supplements (fish oil, vitamin E, Chinese herbs).Keywords: dysmenorrhea, risk factors, adolescence